2012
DOI: 10.1111/j.1600-6143.2011.03891.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Lymphocyte Phenotype After Steroid Avoidance With Either Alemtuzumab or Basiliximab Induction in Renal Transplantation

Abstract: Several studies have analyzed the phenotype of repopulated T-lymphocytes following alemtuzumab induction; however there has been less scrutiny of the reconstituted B-cell compartment. In the context of a randomized controlled trial (RCT) comparing alemtuzumab induction with tacrolimus monotherapy against basiliximab induction with tacrolimus and mycophenolate mofetil (MMF) therapy in renal transplantation, we analyzed the peripheral B-and T-lymphocyte phenotypes of patients at a mean of 25 +/− 2 months after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…This hypothesis has been further strengthened by another work that showed that a significant expansion of regulatory-type B cells (defined as CD19 + CD5 + CD1d high ) is associated with superior graft function and that this pattern is more common after alemtuzumab induction. 45 However, although this hypothesis is interesting, it has been challenged by recent conflicting reports from two independent groups showing that alemtuzumab-induced B cell depletion/reconstitution is associated with a higher incidence of AMR compared with induction with ATG. 46,47 Basiliximab is a chimeric mousehuman nondepleting mAb targeting the a-chain (CD25) of the IL-2 receptor (Figure 1).…”
Section: Effect Of Induction Therapy On Dndsa Generationmentioning
confidence: 76%
“…This hypothesis has been further strengthened by another work that showed that a significant expansion of regulatory-type B cells (defined as CD19 + CD5 + CD1d high ) is associated with superior graft function and that this pattern is more common after alemtuzumab induction. 45 However, although this hypothesis is interesting, it has been challenged by recent conflicting reports from two independent groups showing that alemtuzumab-induced B cell depletion/reconstitution is associated with a higher incidence of AMR compared with induction with ATG. 46,47 Basiliximab is a chimeric mousehuman nondepleting mAb targeting the a-chain (CD25) of the IL-2 receptor (Figure 1).…”
Section: Effect Of Induction Therapy On Dndsa Generationmentioning
confidence: 76%
“…Moreover, we recently showed that stable renal transplant patients with superior graft function, irrespective of immunosuppressive regimen, have higher numbers of both total B cells and TrBs compared with those with reduced renal function. 35 In this study, not only are TrBs reduced in the setting of rejection, but their cytokine profile and functional activity upon in vitro noncognate polyclonal stimulation are abnormal. Closer inspection reveals that most of the patients (80%) in the GD-R group exhibited microvascular inflammation and scarring with or without complement (C4d) deposition, and serologic evidence of circulating donor-specific HLA antibody-all features of CAMR.…”
Section: Discussionmentioning
confidence: 98%
“…Another study by Welberry Smith et al (9) using AZ and tacrolimus monotherapy also found lower BPAR relative to basiliximab, tacrolimus, and mycophenolate mofetil (10%/58 versus 24%/58; P=0.05). Cherukuri et al (10) found that AZ resulted in significantly less BPAR compared with basiliximab with both groups having similar tacrolimus levels and mycophenolate mofetil dosage (10.3%/51 versus 24.1%/45, For overall patient survival 13,752 observations out of 14,025 were used in the model. aHR, adjusted hazard ratio; 95% CI, 95% confidence interval; aOR, adjusted odds ratio; ATG, antithymocyte globulin.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, alemtuzumab (AZ) (Campath-1 H) has been used in kidney transplant immunosuppressive protocols at a number of centers (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Various single and multicenter studies, both randomized and nonrandomized, are reasonably consistent in demonstrating the effectiveness of AZ as an induction or preconditioning agent in renal transplant recipients usually in the context of steroid avoidance or early withdrawal.…”
Section: Introductionmentioning
confidence: 99%